Heuristic Algorithm for Independent Task Scheduling in Grid Computing (International journal of recent technology and engineering, 2019)
Grid enables the integration of large number of geographically distributed heterogeneous resources owned by different organizations for resource sharing and collaboration in solving advanced sciences and engineering applications. In a distributed heterogeneous computing grid environment, scheduling independent tasks on the grid resources is more complicated and is an NP-Complete problem. Scheduling is the process of mapping the tasks to the available resources. In order to utilize the essence of grid efficiently, this paper presents a heuristic technique for scheduling/mapping the tasks to the resources. The efficiency of the proposed algorithm (WSSLVA) in terms of reduced makespan as well as better resource utilization is achieved. The experimental results indicate that the proposed WSSLVA algorithm is a promising algorithm than the Min-min heuristic scheduling algorithm in terms of makespan and resource utilization.